(untitled) (European Journal of Marketing and Economics, 2020)
The problem of measuring the economic security of a country is a complex topic with an ongoing research since there are a number of factors with different characteristics that should be taken into account. The goal of the research is to suggest a model for economic security assessment based on public available data from official sources like EUROSTAT or national databases. The main assumption is that economic security is directly proportional to the economic development. Based on this assumption the economic security could be assessed using measurements for economic development such as GDP, GDP per capita, inflation, unemployment, budget deficit, government debt, net export, etc. A model is provided giving 7 indicators of economic growth and referencing values that if achieved and sustained for a longer period of time should provide a higher level of economic security. Based on the referencing values and comparison with other countries the model could be used for assessing the current level of economic security of a country.